2018
DOI: 10.1016/j.neuint.2018.03.007
|View full text |Cite|
|
Sign up to set email alerts
|

Neuromuscular synapse degeneration without muscle function loss in the diaphragm of a murine model for Huntington's Disease

Abstract: Huntington's disease (HD) is an autosomal dominant neurodegenerative disease characterized by chorea, incoordination and psychiatric and behavioral symptoms. The leading cause of death in HD patients is aspiration pneumonia, associated with respiratory dysfunction, decreased respiratory muscle strength and dysphagia. Although most of the motor symptoms are derived from alterations in the central nervous system, some might be associated with changes in the components of motor units (MU). To explore this hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 61 publications
0
6
0
1
Order By: Relevance
“…Also, this age corresponds to middle age in humans, when it is supposed to appear HD symptoms. In addition, previous work from our research group have shown that 12-month-old BACHD mice present alterations in cardiac cells and other muscles such as STM and diaphragm (Valadão et al, 2017(Valadão et al, , 2018Joviano-Santos et al, 2019).…”
Section: Bachd Micementioning
confidence: 73%
See 2 more Smart Citations
“…Also, this age corresponds to middle age in humans, when it is supposed to appear HD symptoms. In addition, previous work from our research group have shown that 12-month-old BACHD mice present alterations in cardiac cells and other muscles such as STM and diaphragm (Valadão et al, 2017(Valadão et al, , 2018Joviano-Santos et al, 2019).…”
Section: Bachd Micementioning
confidence: 73%
“…However, we judge that a study using females would be valuable, as HD is a disease that affects both sexes and it has already been shown that this disease has slightly faster progression in females than in males (Zielonka et al., 2013). In addition, in a recent study, Zielonka et al. (2018), showed that women with HD have a declining motor function affecting, more severely, on functionality and independence than in men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whole-mount diaphragms were used to evaluate changes in NMJs of MHV-3-infected mice and mock controls. Sample processing and labeling of NMJs were performed based on a previous protocol (49). The pre-synaptic and post-synaptic terminals were stained using the monoclonal anti-synaptotagmin antibody (1:250 dilution, Developmental Studies Hybridoma Bank; cat No.…”
Section: Methodsmentioning
confidence: 99%
“…Conclusion: We concluded that respiratory muscle training may be beneficial for patients with Huntington's disease, but further studies are needed to determine the best protocol for them. Keywords: Huntington's disease, muscle strength, respiratory muscles, walk test, muscle trainning Introdução A Doença de Huntington (DH) é uma doença neurodegerenativa hereditária, caracterizada por alterações motoras, distúrbios psiquiátricos e disfunção cognitiva, causada por expansão do códon CAG (≥37 repetições) do gene de Huntington (IT15), expressa no braço curto do cromossomo 4, cujo início dos sintomas ocorre, geralmente, entre a quarta e quinta década de vida [1].…”
unclassified